Coping strategies to workplace violence among nursing students: a cross-sectional study - Sinh Minh Do; Anh Thi Lan Mai; Mai Thi Thuy Vu (Occupational Health and Safety Society of Nepal, 2024)
Introduction: Nursing students, due to limited clinical practice and challenges in building relationships, are highly vulnerable to workplace violence. Understanding their responses to such incidents is critical, given its significant implications. This study aimed to investigate nursing students' coping strategies for workplace violence in Vietnam Methods: A cross-sectional study was conducted on 776 nursing students conveniently sampled from 10 Vietnamese universities through the KoBotool Box platform. The research instrument has been developed in accordance with findings from several antecedent studies. Frequencies and percentages were used to describe coping strategies, and χ2 test or Fisher's exact test was used to test differences in reporting workplace violence experiences between student groups. Results: Students used a variety of strategies to respond to workplace violence. Trying to stay calm to explain to the perpetrator was the most common strategy (71.8% for physical violence; 40.5% and 36.9% for non-physical violence). The rate of reporting experiences of workplace violence with physical violence and non-physical violence by patients/patients' relatives and non-physical violence directed by medical staff/instructors was 35.9%, 9.5%, and 7.9%, respectively. The most common reason nursing students do not report an incident was because they believe it is part of their clinical placement. Conclusion: Students' response strategies to workplace violence are emotionally oriented and inadequate in their experiences of workplace violence. Appropriate training on how to respond to and report exposure to workplace violence should be provided and or enhanced for nursing students.